The effects of in vitro treatment of melastoma malabathricum on fibroblast proliferation - Abdull Rasad, Mohammad Syaiful Bahari; Kaderi, Mohd Arifin; Mat Alewi, Nur Aizura; Ahmad Roslen, Nurfariza; Abdullah, Samirah (IACSIT Press, 2012)
As the demands in wound care have increased, it is imperative to quickly address this issue at hand. Melastoma malabathricum has been claimed to have astounding treatment in wound repair. This study aims to determine its wound healing potentials by assessing and comparing the rate of proliferation of fibroblasts, before and after, treatment of M. malabathricum’s methanol and aqueous extracts. The study also aims to compare the potential proliferation of cells between different concentrations of extracts through Methylene Blue Assay (MBA). Results were analyzed through two-way ANOVA using SPSS. The results showed a marked proliferation of cells where 39.3 % and 20.7 % were seen at concentrations A3 and A4 respectively. Concentrations A3 and A4 showed a decrease to 13.2 % and 16.4 % at 48 hours to a negligible proliferation at 72 hours, which may indicate probable impairment in the wound treatment. The methanol extracts revealed a gradual dose-response inhibitory effect throughout all the concentrations, accounting for its toxicity effect on cells. This depicts a time and dose-dependent proliferative effect of M. malabathricum’s aqueous extract on fibroblasts, while its methanol extract had a toxic effect on the cells.